Histomorfologi Dan Histomorfometri Otot Ayam Hutan Hijau (Gallus Varius) Asal Pulau Alor - Meica Agatha Leli Paschalya Bengkiuk; Filphin A Amalo; Inggrid T Maha; Heny Nitbani (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Green jungle fowl is one of the endemic animals in Indonesia. One of the distribution areas of green jungle fowl in East Nusa Tenggara is the island of Alor. Until now there has been no research conducted to determine the histological structure of the green jungle fowl so that this study was conducted with the aim of knowing the histological structure and muscle histomorphometry of the green jungle fowl. The research samples were pectoralis and bicep femoris muscles taken from three green jungle fowl in Kalabahi, Alor Regency. Muscle tissue was fixed using 10% formalin, histological preparations were made and stained with hematoxylin and eosin (HE). The results showed that the muscle histomorphology in the transverse section showed that the skeletal muscle of the green jungle fowl was composed of muscle fibers in a polygonal shape with many nuclei at the edges and connective tissue. No intramuscular fat cells were found. In the longitudinal section, it consists of muscle fibers with a light dark line pattern, the cell nucleus is elongated at the edges and connective tissue. The results of muscle histomorphometry, namely the diameter of the muscle fibers, the diameter of the fasciculus and the thickness of the connective tissue in the bicep femoris muscle area were higher than the pectoralis muscle area. The number of muscle fibers in each fasciculus in the bicep pectoralis muscle area is more than in the bicep femoris muscle area. Muscle histomorphometry is influenced by species, breed/race, age, diet, activity level and anatomical location.